Evaluasi Pelaksanaan Kegiatan Surveilans Malaria dalam Mendukung Eliminasi Penyakit Malaria di Kabupaten Kupang - Maria Yosephina Desita; Yuliana Radja Riwu; Ribka Limbu (Universitas Nusa Cendana, 2021)
Malaria Surveillance are formed by system that support the purpose of activity. Purpose of the research was evaluated malaria surveillance activities in support of malaria elimination in Kupang District 2020 based on input, process, output assessment. This Research was descriptive research with qualitative approach. Subjects were malaria surveillance officer in Department of Health in Kupang District, and Batakte, Baumata, Tarus Health Center with using purposive sampling method. This research was conducted August-September 2020. Primary data sources were interviews, observations, while secondary data collected through report documentation. Data analysis was descriptively. The results of study showed that input given were inadequate like human resources, the level of education 66,7% not an epidemiolog, and 100% of double officers. Specifically, the district health office malaria surveillance funds do not sufficient, while in health center is funded from BOK. Malaria surveillance facilities are not available. Process is considered quite good: data collection using weekly and monthly report formats, completeness of reports, and accuracy >80%. The data compilation has described characteristics of people, time, place-data analysis and interpretation by making comparisons the number of cases presented in graph. Output is unsuitable: information like the publication of annual surveillance bulletins is not available, dissemination of information by health office only to cross-programs, health center to cross-program, cross-sector. Feedback has been achieved: health office makes quarterly report and visits health center through small workshops. Suggestions: need to attention that officer education qualifications, surveillance activities facilities, and the publishing of the annual surveillance bulletin.